2012
DOI: 10.1386/tmsd.11.1.67_1
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection in seed potato production in Kenya as a case of successful research-led innovation

Abstract: By identifying the success factors of a programme on positive seed potato selection, this article analyses the role of research in agricultural innovation. The positive seed selection programme developed an approach to improve the quality of seed potatoes by ware potato growers, complementary to specialized seed production systems now widely promoted in sub-Saharan Africa. With more weight being placed on innovation rather than on research outcome, the role of research has been widened and research has assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Many reasons have been given for the failure of certified seed replacement systems in developing countries (Thiele, ). The authors propose that the research and development initiatives that have driven potato seed interventions in developing countries for the last five decades or more (Crissman, ; Crissman et al ., ; Kadian et al ., ; Hidalgo et al ., ; Gildemacher et al ., ) need to be critically scrutinized. The near‐exclusive emphasis on certified seed replacement systems (Fig.…”
Section: Approaches To Degeneration Managementmentioning
confidence: 99%
“…Many reasons have been given for the failure of certified seed replacement systems in developing countries (Thiele, ). The authors propose that the research and development initiatives that have driven potato seed interventions in developing countries for the last five decades or more (Crissman, ; Crissman et al ., ; Kadian et al ., ; Hidalgo et al ., ; Gildemacher et al ., ) need to be critically scrutinized. The near‐exclusive emphasis on certified seed replacement systems (Fig.…”
Section: Approaches To Degeneration Managementmentioning
confidence: 99%
“…Additionally, a technique to maintain or even improve seed quality has been widely advocated and disseminated by the International Potato Center for application in regions where farmer-saved seed is still dominant, such as Eastern Africa. This technique, referred to as positive selection, involves identifying plants that look healthy at an early stage of the season (e.g., at flowering), which will eventually be harvested for seed at the end of the growing season ( Gildemacher et al, 2011 , 2012 ; Schulte-Geldermann et al, 2012 ; Thomas-Sharma et al, 2016 ). The positive selection method is simple, cheap and robust, and can easily be adopted by small-holder seed growers or ware growers who plant their own seed.…”
Section: Crop Management Positive Selection and Regeneration Of Degmentioning
confidence: 99%
“…To address the constraint of seed degeneration, Thomas-Sharma et al (2016) recently outlined such a strategy, within which host plant resistance and on-farm disease management play integral roles. They showed that such an approach, including positive selection and the regeneration of degenerated seed, can be used for designing adequate and sustainable seed systems to improve potato productivity in parts of the world that lack access to a continuous supply of healthy seed ( Gildemacher et al, 2012 ; Schulte-Geldermann et al, 2012 ; Thomas-Sharma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Good farm management can enhance yield and quality of seed potatoes produced by ware/seed growers. For example, a positive seed potato selection study undertaken in Kenya showed that positive seed potato selection increases the yield of potato by ware growers by about 34% (Gildemacher et al, 2012). The current practice in the informal seed system is suboptimal and needs improvement.…”
Section: Seed Potato Farm Managementmentioning
confidence: 99%